Protective Effects of Trimetazidine in Retarding Selenite-Induced Lens Opacification. (2nd December 2019) - Fang, Weifang; Ye, Qin; Yao, Yihua; Xiu, Yanghui; Gu, Feng; Zhu, Yihua
ABSTRACT: Purpose : Cataracts are the leading cause of vision loss worldwide, and the over-production of reactive oxygen species (ROS) is the foremost underlying cause of cataracts. Reducing ROS levels can efficiently prevent lens opacification, as evidenced by many studies. Here, we inhibited ROS overproduction with trimetazidine (TMZ), which is an antioxidant, to explore the therapeutic effects of TMZ and the mechanism of lens opacification. Materials and methods : Sodium selenite-induced cataract formation resulted in a significant loss of lens transparency. This effect could be efficiently rescued by TMZ, which was further found to be an inhibitor of ROS production, as determined by assaying oxidative stress-related parameters (SOD activity, MDA, ·OH and H2 O2 levels) during cataract formation. The experimental protocols involving animal research were approved by the Animal Care and Ethics Committee of Wenzhou Medical University and conducted according to the Association for Research in Vision and Ophthalmology under the guidelines of the Animal Welfare Act (SYXK 2015–0009). Results : Our study found that TMZ can retard the onset and progression of lens opacification in vivo in experiments using Sprague-Dawley (SD) suckling rats and can rescue the morphology of HLEB3 cells in vitro . The flow cytometry and DNA fragmentation assays showed that TMZ could prevent sodium selenite-induced apoptosis. The western blot analysing showed that the levels of apoptosis-associated Bcl-2 and Nrf2 were dramatically decreased following the sodium selenite treatment. In addition, the bisulfate DNA sequencing revealed that the demethylation of CpGs in the promoter region of Keap1 was stimulated, and that this demethylation could be inhibited by TMZ by rescuing the Nrf2 expression level. Conclusions : Our findings indicate that the antioxidant TMZ strongly reduces ROS production, which ultimately delays the progression of cataract formation, suggesting that treatment with TMZ represents a novel, promising antioxidant protection to retard cataract formation.